2004
DOI: 10.4049/jimmunol.172.9.5313
|View full text |Cite
|
Sign up to set email alerts
|

κ Editing Rescues Autoreactive B Cells Destined for Deletion in Mice Transgenic for a Dual Specific Anti-Laminin Ig

Abstract: We explored mechanisms involved in B cell self-tolerance in a double- and triple-transgenic mouse model bearing the LamH-Cμ Ig H chain conventional transgene and a gene-targeted replacement for a functional Vκ8Jκ5 L chain gene. Whereas the H chain is known to generate anti-laminin Ig in combination with multiple L chains, the H + L Ig binds ssDNA in addition to laminin. Immune phenotyping indicates that H + L transgenic B cells are regulated by clonal deletion, receptor editing via secondary rearrangements at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 34 publications
10
38
0
Order By: Relevance
“…Detailed analysis of M6 and M29 lineage mice revealed that LamH transgenic anti-laminin B cells are regulated by central deletion, κ light-chain editing, and anergy [10,74]. Anti-laminin antibodies were not detected in serum or among monoclonal antibodies despite in vitro and in vivo strategies to activate B cells (Tables 3 and 4).…”
Section: Regulation Of B Cell Autoreactivity To Laminin: the Lamh Ig mentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed analysis of M6 and M29 lineage mice revealed that LamH transgenic anti-laminin B cells are regulated by central deletion, κ light-chain editing, and anergy [10,74]. Anti-laminin antibodies were not detected in serum or among monoclonal antibodies despite in vitro and in vivo strategies to activate B cells (Tables 3 and 4).…”
Section: Regulation Of B Cell Autoreactivity To Laminin: the Lamh Ig mentioning
confidence: 99%
“…Most B cells that escaped deletion in M29 mice did so by editing their κ light-chain receptors [10]. Receptor editing is an efficient and common salvage process by which an Ig receptor is replaced by a different receptor through continued Ig gene rearrangements.…”
Section: Regulation Of B Cell Autoreactivity To Laminin: the Lamh Ig mentioning
confidence: 99%
See 2 more Smart Citations
“…Autoimmune diseases afflict most organ systems and impose an enormous burden on the health care system (1).…”
mentioning
confidence: 99%